Parcel locker stations: A solution for the last mile? - Antonia Niederprüm; Willem van Lienden (WIK Wissenschaftliches Institut für Infrastruktur und Kommunikationsdienste, 2021)
Postal outlets and parcel shops are increasingly complemented by parcel locker stations. This paper explores the potential reasons for varying trends in the use of parcel locker stations in Europe and discusses the role of parcel locker stations in e-commerce delivery. The paper aims to identify challenges and key drivers for the development of networks of parcel locker stations based on case studies for a selection of countries. It analyses typical business models and discusses the economic reasons for the dominance of exclusively operated networks. The country studies show that establishing a parcel locker network requires significant investments and a dedicated digital strategy by the respective operators. We expect that the increased use of parcel locker stations in Germany will require significant incentives to motivate users (senders and recipients) in choosing this delivery method above home delivery.
Keywords: L20; L81; L87; 380; Parcel locker stations; e-commerce delivery; delivery option